2015
DOI: 10.1021/acs.analchem.5b01656
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Disassembly of Self-Quenched Nanoparticles Turns NIR Fluorescence on for Sensing Furin Activity in Cells and in Tumors

Abstract: There has been no report on enzyme-controlled disassembly of self-quenched NIR fluorescent nanoparticles turning fluorescence on for specific detection/imaging of the enzyme's activity in vitro and in vivo. Herein, we reported the rational design of new NIR probe 1 whose fluorescence signal was self-quenched upon reduction-controlled condensation and subsequent assembly of its nanoparticles (i.e., 1-NPs). Then disassembly of 1-NPs by furin turned the fluorescence on. Employing this enzymatic strategy, we succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 34 publications
1
40
0
1
Order By: Relevance
“…Furthermore, furin has been demonstrated to cleave “smart” imaging agents. Thus, furin‐induced cleavage leads to condensation and self‐assembly of gadolinium‐based or radioactive‐labelled nanoparticles, which might be used for tumour‐specific magnetic resonance imaging (MRI) or positron emission tomography (PET), respectively …”
Section: Furin Is a Tool For Cancer Cell‐specific Therapeutic Approachesmentioning
confidence: 99%
“…Furthermore, furin has been demonstrated to cleave “smart” imaging agents. Thus, furin‐induced cleavage leads to condensation and self‐assembly of gadolinium‐based or radioactive‐labelled nanoparticles, which might be used for tumour‐specific magnetic resonance imaging (MRI) or positron emission tomography (PET), respectively …”
Section: Furin Is a Tool For Cancer Cell‐specific Therapeutic Approachesmentioning
confidence: 99%
“…The experimental results in vitro and in vivo showed that this strategy could improve the signal‐noise ratio and sensitivity for responding the biological enzyme activity. Furthermore, a series of peptide‐functionalized AIEgens were also reported for detection of biomarkers such as integrin α v β 3 , caspase, furin, Mdm2, ER protein, TfR, sirtuin type 1, chymase, LAPTM4B protein, and transferrin (TrF) …”
Section: Key Application In Biomedicinementioning
confidence: 99%
“…Among the various amino acid residues containing potentially reactive nitrogen atoms, we targeted lysine because of its nucleophilicity and unambiguous site of reactivity. Strategies used for the chemical modification of primary amines in polypeptides include conjugate addition, 5 condensation with an activated ester, 6 addition to a (thio)isocyanate or ketene, 7 and Schiff base formation/derivatization. 8 More recently, the reaction of acyl trifluoroborates with prefunctionalized hydroxylamine esters has also been reported.…”
mentioning
confidence: 99%